Applications of noninvasive prenatal testing in vanishing twin syndrome pregnancies after treatment of assisted reproductive technology in a single center. (30th November 2020) - Zou, Yang; Cui, Linlin; Xue, Mengyang; Yan, Junhao; Huang, Miao; Gao, Ming; Gao, Xuan; Gao, Yuan; Chen, Zi‐Jiang
Abstract: Objective: The objective of the study is to assess the clinical application of noninvasive prenatal testing (NIPT) for VTS pregnancies after the treatment of assisted reproductive technology (ART). Method: This was a retrospective study on VTS pregnancies through ART treatment. Participants underwent NIPT at 11 to 13 weeks gestation by sequencing. Resampling was recommended for both positive and testing failure cases. For NIPT positive results, participants were advised to have invasive testing. Clinical outcomes were obtained by telephone interview. Results: In total of 579 cases, testing failure rates after first sampling and resampling were 7.6% and 1.4%, respectively. Twelve positive results were reported by NIPT. But only one true positive was confirmed, giving a PPV of 8%. A total of 576 cases completed the follow‐up (including 533 NIPT negative, 12 positive, and 31 testing failure) and three cases lost follow‐up. Among the 536 cases with NIPT negative results, 504 (94.0%) resulted in live‐birth and 29 (5.4%) resulted in miscarriage or stillbirths. No false‐negative result was reported. Conclusion: NIPT has the potential to be used in prenatal screening for VTS pregnancies. For the pregnant women who obtained positive and testing failure results, resampling after 15 weeks of gestation is recommended.